Citizen satisfaction survey as a tool of citizen relationship management of local government in Slovakia - Fila, Milan; Schwarcova, Loreta; Mura, Ladislav (Serbian Journal of Management, 2015)
Citizen Relationship Management (hereinafter referred to as CiRM) becomes increasingly important in the countries of so called post-communist Europe nowadays. The communication process in the citizen – municipality relationship is at present no longer about one-way informing of the citizens about orders, prohibitions or obligations. People want to be informed and to be at the heart of the process. At the same time, considering the democratic development of society and modern technical means, they also feel the need both to actively participate in the public life through expressing their opinions, comments or suggestions, and to influence the development of the environment in which they live. Not only enterprises but also the state and public administrations and regional and local self-governments inevitably have to adapt to it. Based on the research carried out in the cities of the SR, in which currently approximately 55% of all citizens of Slovakia live, the presented scientific paper evaluates the current state, level and the importance of the conduct of local citizen satisfaction surveys in relation to local governments as a tool of the CiRM managed by the municipal authorities or by any persons or institutions authorized by them. This paper also points out several deficiencies it entails particularly in the area of publication of identified findings by the cities of the SR.